If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 2) + -3(5x + -2) = 26 Reorder the terms: 7(2 + x) + -3(5x + -2) = 26 (2 * 7 + x * 7) + -3(5x + -2) = 26 (14 + 7x) + -3(5x + -2) = 26 Reorder the terms: 14 + 7x + -3(-2 + 5x) = 26 14 + 7x + (-2 * -3 + 5x * -3) = 26 14 + 7x + (6 + -15x) = 26 Reorder the terms: 14 + 6 + 7x + -15x = 26 Combine like terms: 14 + 6 = 20 20 + 7x + -15x = 26 Combine like terms: 7x + -15x = -8x 20 + -8x = 26 Solving 20 + -8x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -8x = 26 + -20 Combine like terms: 20 + -20 = 0 0 + -8x = 26 + -20 -8x = 26 + -20 Combine like terms: 26 + -20 = 6 -8x = 6 Divide each side by '-8'. x = -0.75 Simplifying x = -0.75
| 20x+15y=2750 | | 2x+3y=-0 | | 3x+4(-3)=0 | | 3(x-4)+7=4x+5 | | 8x-37=2x+35 | | 6(y+38)-19=43 | | 3x+32=2x+26 | | 5(3x+2y)= | | 15025=45.5t^2+6100 | | -36-6x=7x+2x | | 10n^2-6=994 | | 5(7x+5)whenx=10solve | | 85=(x)(4x-3) | | 10n^2=994 | | N^2+9n+15=7 | | (x+5)+(2x+15)+(2x+10)=90 | | 5(2x-2)=3x+11 | | x(4x+13)=-3 | | x+(X*.10)=1280418 | | 5x+2x^2+2=0 | | h(t)=-4.9t^2+32+2 | | 4x-15+3x=5+7x-19 | | -4p+11-(-5p)-2= | | 36x^2-36x-216=0 | | 400+50x=4000 | | -81=-4+7(6b-5) | | y+4=0.5x+1 | | -7y+12+2y-1= | | 6(x+3)-8x=36 | | 4(8k+5)= | | (3x-5)(2x+8)= | | (x+3)(x+3)=X^2+81 |